2022
DOI: 10.3389/fevo.2022.854497
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Future Climate and Land Use/Cover Changes on Water-Related Ecosystem Services in Changbai Mountains, Northeast China

Abstract: Sustaining ecosystem services in alpine regions is a pressing global challenge given future accelerating environmental changes. Understanding how future climate change and land use/cover change (LUCC) drive ecosystem service will be important in this challenge. However, few studies have considered the combined effects of future climate change and LUCC on ecosystem services. We assessed water yield and soil retention services and their drivers in the Changbai mountains region (CBMR) from the 2020 to 2050s using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Human activities could affect sustainable ecosystem services; for example, agriculture negatively influences water quality (Anderson et al, 2021), biodiversity (Sharma et al, 2018), carbon stocks, and soil retention (Wang et al, 2022). Consequently, the growth of agricultural land, specifically intensive agriculture, is often considered an enemy of sustainable water ecosystem services due to the production of pollutants, including fertilizer and chemical inputs (Rashmi et al, 2020), as well as the tendency to reduce water supply through irrigation (Munyaradzi et al, 2022).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Human activities could affect sustainable ecosystem services; for example, agriculture negatively influences water quality (Anderson et al, 2021), biodiversity (Sharma et al, 2018), carbon stocks, and soil retention (Wang et al, 2022). Consequently, the growth of agricultural land, specifically intensive agriculture, is often considered an enemy of sustainable water ecosystem services due to the production of pollutants, including fertilizer and chemical inputs (Rashmi et al, 2020), as well as the tendency to reduce water supply through irrigation (Munyaradzi et al, 2022).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Studies on the factors that influence water conservation services have shown that these are complex and diverse, but can be broadly divided into natural environmental factors and human activity factors. Precipitation and evapotranspiration are two important climatic factors that directly affect regional water conservation [36,53,54], while temperature indirectly affects the water conservation process by influencing water evaporation [11]. Forestlands and grasslands also influence water conservation because of the water interception, storage, and evapotranspiration effects of vegetation [17,53].…”
Section: Geographically Weighted Regression Modelmentioning
confidence: 99%
“…LUCC is a nonlinear change process that is highly compounded and impacted by multi-factor subsystems, such as natural ecology, the economy, society, and policy formulation and implementation. It can directly represent the external performance of mutual feedback between the natural environment and human activities, which can lead to abrupt changes in the spatiotemporal characteristics of ecological subsystems, such as aquatic ecology [ 16 , 17 , 18 ], atmospheric environment [ 19 ], and species [ 20 ]. The ecological impact of LUCC will lead to changes in the spatial and temporal characteristics of the ecological landscape pattern, resulting in ecological risks [ 21 , 22 , 23 ], such as ecological degradation and soil dehydration.…”
Section: Introductionmentioning
confidence: 99%